Beneficial effects of gluten free diet in potential coeliac disease in adult population. Issue 8 (August 2017) - Imperatore, Nicola; Tortora, Raffaella; De Palma, Giovanni Domenico; Capone, Pietro; Gerbino, Nicolò; Donetto, Sara; Testa, Anna; Caporaso, Nicola; Rispo, Antonio
Abstract: Background: To date, potential coeliac disease (PCD) occurring in adults remains an almost unexplored condition. Aims: To explore the prognostic role of Marsh grade in adult PCD patients, and to evaluate the effects of gluten-containing diet (GCD) in asymptomatic PCD patients. Methods: We retrospectively evaluated all consecutive adult PCD patients followed-up for at least 6 years. Patients were divided into: Group A (patients with Marsh 0 histology) and Group B (Marsh 1 patients). Symptomatic patients were started gluten-free diet (GFD), while asymptomatic subjects were kept on GCD and were followed-up. Results: 56 PCD patients were enrolled (21 in Group A and 35 in Group B). Forty-three patients were symptomatic and started GFD. Of these, none of 15 patients in Group A and 8 of 28 patients in Group B developed immune-mediated disorders (IMD) during follow-up (P = 0.03; OR = 4.2). The 13 asymptomatic PCD patients were kept on GCD. During the follow-up, 9 patients developed CD-related symptoms, 6 villous atrophy and 8 IMD. At the end, patients kept on GCD were at higher risk of developing IMD than those following a GFD (61% vs 18%, P = 0.03, OR = 3.3). Conclusions: Although PCD with normal mucosa seems to be a milder disease, the continuation of GCD places patients at a high risk of developing villous atrophy and IMD compared to commencement of GFD. Adult PCD patients should start GFD even if not symptomatic.